Dietary Nutrient Intake and Obesity Prevalence among Native American Adolescents - Hanchu Dai; Randy Song; Margaret Barth; Shasha Zheng (Intelektual Pustaka Media Utama, 2018)
The prevalence of obesity among adolescent minority populations has been long recognized, but little research has been done on Native Americans adolescents. Using anthropometric measurements and dietary assessments, the findings within each study have shown to obtain baseline measures to determine the prevalence of obesity within the Sherman Indian High School’s Native American adolescent population. Data of each assessment appear to be of use for predicting obesity and creating effective future interventions. Compiling data using the Harvard School of Public Health Youth/Adolescent Questionnaire (HSPH YAQ), a semi-quantitative food frequency questionnaire allowed significant data to be found between normal and obese weight students. Utilizing each finding allows more effective ways of targeting and reversing the inclining rate of obesity among Native American adolescents. Results show that antioxidants being examined on such as vitamin E and lycopene are beneficial in lowering the obesity rate among Native American adolescents. Levels of fiber, thiamin and folate consumption was significantly lower among the obese population in Sherman Indian High School’s Native American adolescents. Moreover, dietary mineral intake was shown to be lower among obese Native American adolescents comparing with the normal weight group. The results suggested that dietary consumption of these nutrients might correlate and predict obesity and lead to the development of effective interventions for Native Americans. This study also found the effects of total fiber and vitamin B in diets with lifestyle intervention in prediabetic adults, showing that total fiber intake among the normal weight students is significantly higher than obese students, indicating that fiber and vitamin profile could be important determinants of the effect of dietary intervention.